THE FORMATION OF FUTURE PSYCHOLOGISTS’ PROFESSIONAL ASPIRATIONS IN THE PROCESS OF STUDYING THE DISCIPLINE «PEDAGOGY AND PSYCHOLOGY OF HIGHER SCHOOL» - Nataliia P. Volkova; Olena O. Lavrentieva (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
In the article the problem of theoretical and methodological aspects, factors and means of forming the future psychologists’ professional aspirations have been revealed. The characteristics, content and essence of the «aspirations» and «professional aspirations» concepts have been clarified and analysed. It has been determined that professional aspirations are a complex personal phenomenon, which is a set of requirements, expectations that a person feels and experiences in relation to his/her own professional life and his/her own future. It is the person’s ability to model the desired future in accordance with the expectations of society, without giving up their own potentials and plans, as well as certain individual standards of future life, which a person already deserves today. The components of professional aspirations have been shown. Among them are the motivational component (the complex of motives, needs, guidelines in professional activities), the cognitive one (knowledge of the content and structure of professional aspirations, their impact on professional readiness and success of the specialist, as well as the methods and technologies of their formation), the activity one (the degree of formation of the organizational, psychology and diagnostic, prognostic, reflexive, and communicative skills) and the reflexive one (the structure of reflexive, critical and creative thinking of future psychologists). It has been established that among the components of the educational program of future psychologists’ professional training, the discipline «Pedagogy and psychology of higher school» has significant potential in the formation of students’ professional aspirations. For that, the educational process should be organized taking into account such requirements as subjectivity, dialogical nature, developmental orientation, interaction in the subsystems «lecturer - student», «student - student», which is based on co-creation and cooperation, equality of positions, empathy. It has been empirically confirmed that the formation of master degree students’ professional aspirations is possible thanks to the updated content, as well as by way of providing a link between theoretical and practical preparation in the teaching of this discipline. In the article it has been shown that, for this purpose, it is advisable to combine lectures (lecture-conversation, lecturediscussion, problem lecture), seminars (seminar in «small groups», seminar - reflection) and practical classes using a number of pedagogical technologies, namely: dialogue and discussion ones (dispute, debate, round table), game ones (role-games, simulation games, projecting-ingame), training ones (developmental, game, and simulation trainings), problem and situation learning (case-studies, projects, portfolios), blended learning (thematic blog, web-quest, search online, webinar). The diagnostic data obtained upon completion made it possible to state the positive and statistically significant dynamics in the components of future psychologists’ professional aspirations. The conclusion has been made on the expediency of construction of conceptual bases of the information and development environment of HEI, which is aimed at professional training of highly skilled and professionally self-realized experts and development of their professional aspirations.